1998
DOI: 10.1046/j.1365-2958.1998.00980.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Pseudomonas aeruginosa hemF and hemN by the dual action of the redox response regulators Anr and Dnr

Abstract: SummaryThe oxidative decarboxylation of coproporphyrinogen III catalysed by an oxygen-dependent oxidase (HemF) and an oxygen-independent dehydrogenase (HemN) is one of the key regulatory points of haem biosynthesis in Pseudomonas aeruginosa. To investigate the oxygen-dependent regulation of hemF and hemN, the corresponding genes were cloned from the P. aeruginosa chromosome. Recognition sequences for the Fnr-type transcriptional regulator Anr were detected ¹44.5 bp from the 5Ј end of the hemF mRNA transcript a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 51 publications
8
83
1
Order By: Relevance
“…-Surprisingly, the HEM13 gene of yeast and the hemF gene of Pseudomonas aeruginosa both encoding oxygen-dependent CPOs are drastically induced under anaerobic growth conditions (22,23). Similar findings were described for oxygen-dependent ribonucleotide reductase from E. coli (24).…”
Section: Oxygen-loaded E Coli Hemf Allows One Catalytic Turnover Undmentioning
confidence: 59%
“…-Surprisingly, the HEM13 gene of yeast and the hemF gene of Pseudomonas aeruginosa both encoding oxygen-dependent CPOs are drastically induced under anaerobic growth conditions (22,23). Similar findings were described for oxygen-dependent ribonucleotide reductase from E. coli (24).…”
Section: Oxygen-loaded E Coli Hemf Allows One Catalytic Turnover Undmentioning
confidence: 59%
“…In addition to hcnA and PA1557, two other genes that were AlgR dependent in the transcriptional profiling analysis (Tables 2 and 4) are known to be ANR dependent. The arcDABC operon, which encodes the anaerobic arginine deiminase enzymes (22), and hemN, which encodes the oxygen-independent coproporphyrinogen III oxidase (49), are both ANR dependent. None of the conditions that we examined by transcriptional profiling revealed that anr was AlgR regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the authors (30) demonstrated that hemN is highly expressed in A. eutrophus cells grown anaerobically on nitrate and only weakly expressed in aerobic cells. Negative regulation of the hemN expression by oxygen was also observed in E. coli (31) and Pseudomonas aeruginosa (32). On the other hand, no obvious oxygen regulation was observed for the Bacillus subtilis hemN gene (33).…”
Section: Figmentioning
confidence: 91%